2022
DOI: 10.35812/cellulosechemtechnol.2022.56.22
|View full text |Cite
|
Sign up to set email alerts
|

"Comparative Isoconversional Thermal Analysis and Degradation Kinetics of Salvia Spinosa (Kanocha) Seed Hydrogel and Its Acetates: A Potential Matrix for Sustained Drug Release"

Abstract: The present study deals with the isolation and modification of Salvia spinosa hydrogel (SSH) to investigate its thermal degradation profile. The SSH was modified chemically to its acetylated derivative (ASSH-1–4) with DS 1.05-2.79. After characterization by Fourier transform infrared (FTIR) and solid-state CP/MAS 13C-NMR spectroscopic techniques, both SSH and ASSH-4 were subjected to thermogravimetric analyses (TG) by the isoconversional method, i.e., the Flynn-Waal-Ozawa (FWO) and the Kissinger methods. TG cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The values of thermal decomposition of SSH-co-MAA are high and it degraded majorly in 350-500 °C range which is higher band even than the precursor, SSH. 15 Therefore, these ndings indicated that the graing of MAA onto SSH yielded thermally stable copolymer which expected to have higher shelf life hence, such materials can be stored over a long period of time. Furthermore, the loading of venlafaxine HCl onto SSH-co-MAA did not alter the stability of copolymer and vice versa.…”
Section: Synthesis Of Ssh-co-maa and Reaction Mechanismmentioning
confidence: 94%
See 4 more Smart Citations
“…The values of thermal decomposition of SSH-co-MAA are high and it degraded majorly in 350-500 °C range which is higher band even than the precursor, SSH. 15 Therefore, these ndings indicated that the graing of MAA onto SSH yielded thermally stable copolymer which expected to have higher shelf life hence, such materials can be stored over a long period of time. Furthermore, the loading of venlafaxine HCl onto SSH-co-MAA did not alter the stability of copolymer and vice versa.…”
Section: Synthesis Of Ssh-co-maa and Reaction Mechanismmentioning
confidence: 94%
“…Drug release kinetics and mechanism. The venlafaxine HCl release data was put into the zero-order (eqn (11)), rst-order (eqn ( 12)), Hixson-Crowell (eqn (13)), Higuchi (eqn ( 14)), and Korsmeyer-Peppas (eqn (15)) kinetic models to determine the kinetics and mechanism of venlafaxine HCl release from VSSH-co-MAA.…”
Section: Porosity Measurementmentioning
confidence: 99%
See 3 more Smart Citations